Hodgkin’s Disease Diagnosed in Third Trimester of Pregnancy Coexisting with Pregnancy Cholestasis: Case Report - Boynukalın, Fazilet Kübra; Karahanoğlu, Ertuğrul; Baykal, Cem (Gynecology Obstetrics & Reproductive Medicine, 2014)
As Hodgkin’s disease is well known as a young people neoplasia, it is rarely seen in pregnancy as other malignancies. Sometimes it is complicated with other diseases and its diagnosis is somewhat challenging. Cholestasis of pregnancy is simply diagnosed with mildly elevated liver function tests, plasma bile salts with pruritus. Our case evaluates third trimester Hodgkin’s disease complicated with pregnancy cholestasis.